Carvedilol prevents ovariectomy-induced myocardial contractile dysfunction in female rat. - Rogerio Faustino Ribeiro; Felipe F Potratz; Brunella M M Pavan; Ludimila Forechi; Filipe Lugon Moulin Lima; Jonaina Fiorim; Aurelia Araujo Fernandes; Dalton Valentim Vassallo; Ivanita Stefanon (PLoS ONE, 2013)
Carvedilol has beneficial effects on cardiac function in patients with heart failure but its effect on ovariectomy-induced myocardial contractile dysfunction remains unclear. Estrogen deficiency induces myocardial contractile dysfunction and increases cardiovascular disease risk in postmenopausal women. Our aim was to investigate whether carvedilol, a beta receptor blocker, would prevent ovariectomy-induced myocardial contractile dysfunction. Female rats (8 weeks old) that underwent bilateral ovariectomy were randomly assigned to receive daily treatment with carvedilol (OVX+CAR, 20 mg/kg), placebo (OVX) and SHAM for 58 days. Left ventricle papillary muscle was mounted for isometric tension recordings. The inotropic response to Ca(2+) (0.62 to 3.75 mM) and isoproterenol (Iso 10(-8) to 10(-2 )M) were assessed. Expression of calcium handling proteins was measured by western blot analysis. Carvedilol treatment in the OVX animals: prevented weight gain and slight hypertrophy, restored the reduced positive inotropic responses to Ca(2+) and isoproterenol, prevented the reduction in SERCA2a expression, abolished the increase in superoxide anion production, normalized the increase in p22(phox) expression, and decreased serum angiotensin converting enzyme (ACE) activity. This study demonstrated that myocardial contractile dysfunction and SERCA2a down regulation were prevented by carvedilol treatment. Superoxide anion production and NADPH oxidase seem to be involved in this response.